Early failure of cement with loosening and dislocation of the femoral component in a unicompartmental knee replacement: a case report with microscopic assessment - Mancuso, Francesco; Di Benedetto, Paolo; Colombo, Elia; Miani, Enrick; Fedrizzi, Lorenzo; Buttironi, Michele Mario; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2022)
Background Medial unicompartimental knee artrhoplasty (UKA) is a valuable and well-known option in the treatment of medial osteoarthritis (OA). Early recovery and good results are usually reported. Failure mechanism include septic and mechanical loosening, bearing dislocation and lateral or patello-femoral joint OA evolution. The rare case of an atraumatic dislocation of the cemented femoral component of a UKA is presented together with a literature review and a microscopic analysis of the loosened component. Methods The case of a 60-years old man who suffered a UKA failure due to a complete loosening and migration of the cemented femoral component 5 months after its implantation is reported. A review of the literature pertaining early similar catastrophic failures is discussed. Furthermore a stereo-microscopic and scanning electronic microscopic evaluation of the femoral component was performed. Results A UKA-to-TKA revision was performed. Septic loosening was ruled out and one-year follow up showed patient satisfaction with good clinical and radiographic results. Few cases of complete dislocation of the UKA femoral component are reported in the literature. Macro- and microscopic evaluation showed an almost completely smooth surface at the cemented surface of the posterior condyle of the femoral component. Conclusions Whilst mobile bearing dislocation is a well-known complication of UKA, few cases of this potentially catastrophic complication are reported in the literature. Early UKA failure with complete implant loosening may be determined by a suboptimal cementing technique with inadequate cement penetration into the trabecular bone. In the present case, the absence of cement penetration into the posterior condyle may be one of the reason of the component dislocation after standing up starting with the knee in a highly flexed position.